Comment: Association Between Psoriasis and Non-Alcoholic Fatty Liver Disease: A Two-Sample Mendelian Randomization Study: Comment from Li et al [Letter] - He A; Li H; Zhao X (Dove Medical Press, 2024)
Ao He,* Hainan Li,* Xian Zhao Department of Plastic Surgery, Affiliated Calmette Hospital of Kunming Medical University, Kunming, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xian Zhao, Department of Plastic Surgery, Affiliated Calmette Hospital of Kunming Medical University/Kunming First People’s Hospital, 1128# Beijing Road, Panlong District, Kunming, Yunnan, 650000, People’s Republic of China, Tel +86-1831-3310129, Email 18313310129@163.com